Avaliação da Arquitetura da Informação do Portal de Periódicos da Universidade Federal do Maranhão - Rocha, Carin Cunha (2021)
Digital information and communication technologies have, over time, played a major role in society, generating more research, science and technology. Brazilian universities have followed this technological evolution, making their journals available in electronic form, among other sources, including the grouping of these in portals, considered to be open standardized access environments that assist the management of journals. In this scenario of standardization, Information Architecture comes into play with the objective of organizing digital information environments, aiming to improve information retrieval and user satisfaction, acting as complex and interdisciplinary. This research has as its general objective to evaluate the Information Architecture of the Portal of Journals of the Federal University of Maranhão taking into account the architectural, systemic, informational and pervasive approaches. Specifically, it seeks to evaluate the usability of the Portal, according to the architectural approach; identify the essential components of Information Architecture, according to the systemic approach; analyze the environment according to the pillars of Information Architecture (users, content and context), according to the informational approach; investigate the attributes of the Pervasive Information Architecture present in the informational environment. Methodologically, the following instruments were used: a checklist to assess usability in the architectural approach; a checklist to identify the essential components of Information Architecture in the systemic approach and, finally, an electronic questionnaire aimed at internal users to investigate the attributes of Pervasive Information Architecture present in the environment. For the analysis of the informational approach, an observation was made in order to identify the users, the content and the context of the Portal to organize them in a conceptual map. The results showed the Portal's strengths and weaknesses, and improvements are suggested for the problems encountered. It is concluded that this holistic assessment of Information Architecture constitutes a broad research perspective that may contribute to the literature in this area and support new research.